Analysis of Factors Influencing Continuance Intention in the Use of E-Wallets Among Students of Universitas Islam Indonesia - Ardimas Aryo Kuncoro; Kartini Kartini (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the effect of performance expectancy, effort expectancy, hedonic motivation, and habit on continuance intention to use e-wallets among students of Universitas Islam Indonesia. This research employs a quantitative approach using a survey method through the distribution of online questionnaires to 163 respondents, who are active students and e-wallet users. The data analysis technique used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software. The results show that performance expectancy, effort expectancy, hedonic motivation, and habit have a positive effect on continuance intention to use e-wallets, with habit being the most significant factor. This indicates that the habitual use of e-wallets in daily activities is the main driver of continued usage, in addition to perceived usefulness, ease of use, and the enjoyable experience perceived by users. These findings suggest that the continuance of e-wallet usage is not only influenced by functional aspects but also by behavioral and user experience factors. This study contributes theoretically to the development of the UTAUT2 model in the context of university students in Indonesia and provides practical implications for e-wallet service providers to improve user retention through enhancing user experience and fostering usage habits.